Literasi Manfaat Program Beasiswa Pendidikan STMA Trisakti - Yohanes Jhony Kurniawan; Heppy Julianto (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This Community Service research is based on the material and non-material benefits of the scholarships, so literacy on the benefits of the educational scholarship program at STMA Trisakti is required. With the existence of literacy on the benefits of the educational scholarship program at STMA Trisakti, it is hoped that there will be an increase in understanding among the community, especially the lower middle class, about alternative financing opportunities with scholarships for those who are the targets of the scholarship. Title as follows; "Literacy Benefits of the STMA Trisakti Education Scholarship Program". The Community Service Method uses scholarship benefits literacy by socializing and creating scholarship benefits books. The conclusion is; There are 99 scholarship recipient students who are actively involved in literacy outreach activities for the benefits of the STMA Trisakti Education scholarship, and of the 99 students there are 90 students who write and collect articles or 90, 90% reflect the wishes of scholarship recipient students in literacy activities for the benefits of the STMA Trisakti Education scholarship which is ultimately useful for people who need information from literacy as an outcome. There are 45 articles or 39% that have the appropriate format to be formatted into a final draft of the article with the title inspiration for the benefits of STMA Trisakti Education scholarships. The suggestion is that students have high interest in writing ISBN books, so there is a need for facilitation in achieving academic and non-academic achievements in writing ISBN books